Aspects of Media “Mass-Entertainment” in Contemporary Romania - Dinu, Elena Lidia (Calitatea Vieții, 2016)
In this article we analyze and discuss the Romanian entertainment industry, which has recently led – and for a good reason – to a public space reorganization. Whilst playing a main role in people’s lives, it has managed to change the behaviour, life choices and ways of living of each individual. By taking a huge interest in entertainment, Romanian stars intend to show the society what they have achieved so far and what kind of projects they have, sharing the most important events in their lives with the general public on TV, in the newspapers and in the magazines. At the same time they expose themselves to the risk of misrepresentation and distortion of facts due to oversized mediatization.